Acupuntura como tratamiento coadyuvante en la hipertensión arterial - Alarcón Sangache, Juan Fernando (2025)
Acupuncture is a traditional Chinese medicine technique that involves the insertion of thin needles into specific points of the body. The World Health Organization (WHO) has recognized acupuncture as an ancient therapy with scientific evidence supporting its benefits in reducing high blood pressure. Objective: To demonstrate the efficacy of acupuncture as a coadjuvant treatment in arterial hypertension, in order to improve the protocol for patient care. Methods: A non-descriptive experimental study was carried out in which bibliographic reviews were analyzed and selected, using scientific articles from updated scientific databases, including varied research results, using inclusion and exclusion criteria on arterial hypertension as an adjuvant treatment in arterial hypertension. Results: A personalized approach was carried out, obtaining 63 bibliographies, where 12 updated bibliographies stood out. Articles that are not in accordance with the required time period, articles on hypertension associated with diabetes, hypertension associated with renal failure, articles at high cost, articles on hypertensive treatment with ancestral medicine, acupuncture and hypertension, hypertensive treatment with acupuncture, treatment with ancestral medicine for hypertension were included. Conclusions: The reviewed bibliography managed to highlight that arterial figure improve with acupuncture, in such a way that they serve as a coadjuvant treatment, taking into account, lifestyle changes, pharmacological treatments and risk factors. At present, giving opportunity for future research and advances in this field.